Legal Protection of Personal Data Financial Technology Based Online Loans from The Consumer Protection Act - Noptabi, Iim Saputra; Aprita, Serlika; Wulandari, Mona (Universitas Islam Negeri Walisongo Semarang, 2022)
This study aims to determine the legal protection of personal data financial technology (Fintech) based on online loans in terms of the Consumer Protection Act and what are the legal consequences of personal data violations by fintech companies based on online loans in terms of the Consumer Protection Act. The type of research used is normative legal research. The conclusion of this study is that the legal protection of consumer personal data has been regulated by the Financial Services Authority (OJK) Circular and the Regulation of the Minister of Communication and Information concerning Confidentiality, Integrity and Security of Consumer Personal Data or Information and the Legal Consequences of Personal Data Violation, which is regulated in Article 47 of the Authority Regulation. Financial Services Number 77/POJK.01/2016 is an administrative sanction, then there is the Personal Data Protection Bill which regulates criminal sanctions. Penelitian ini bertujuan untuk mengetahui perlindungan hukum data pribadi financial technology berbasis pinjaman online ditinjau dari Undang-Undang Perlindungan Konsumen dan bagaimana akibat hukum pelanggaran data pribadi yang dilakukan perusahaan fintech berbasis pinjaman online ditinjau dari Undang-Undang Perlindungan Konsumen. Jenis penelitian yang digunakan adalah penelitian hukum normatif. Kesimpulan penelitian ini adalah perlindungan hukum data pribadi konsumen telah diatur oleh Surat Edaran Otoritas Jasa Keuangan (OJK) dan Peraturan Menteri Komunikasi dan Informatika tentang Kerahasiaan, Keutuhan dan Keamanan Data atau Informasi Pribadi Konsumen dan Akibat Hukum Pelanggaran Data Pribadi yaitu diatur dalam Pasal 47 Peraturan Otoritas Jasa Keuangan Nomor 77/POJK.01/2016 adalah sanksi administratif, lalu terdapat Rancangan Undang-Undang Perlindungan Data Pribadi yang mengatur sanksi pidana.